Analysis Of Implementation Of Sharia Accounting Standards Of PSAK No. 101 On Financial Transactions Managed At Sharia Bank (Study On BRI Syariah Bank Lhokseumawe Branch) - Novia Tri Ramadhani; Nana Diana (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study is to find out how the application of Islamic accounting standards to financial transactions that are managed and a comparison of the application of Islamic accounting standards applied by PT. Bank BRI Syariah Lhokseumawe Branch with PSAK NO.101. The object of this research is PT. Bank BRI Syariah Lhokseumawe Branch. This research was conducted using a qualitative descriptive method through case studies at PT. Bank BRI Syariah Lhokseumawe Branch. The data used is primary data on interview form. The results of this study indicate that there is no significant difference between implementation of sharia accounting standards implemented by Bank BRI Syariah Lhokseumawe Branch with PSAK NO.101.